Resting sympatho-vagal balance is related to 10 km running performance in master endurance athletes - Angelo Cataldo; Antonino Bianco; Antonio Paoli; Dario Cerasola; Saverio Alagna; Giuseppe Messina; Daniele Zangla; Marcello Traina (PAGEPress Publications, 2018)
Relationships between heart rate recovery after exercise (HRR, baseline heart rate variability measures (HRV), and time to perform a 10Km running trial (t10Km) were evaluated in "master" athletes of endurance to assess whether the measured indexes may be useful for monitoring the training status of the athletes. Ten "master" athletes of endurance, aged 40-60 years, were recruited. After baseline measures of HRV, the athletes performed a graded maximal test on treadmill and HRR was measured at 1 and 2 minutes from recovery. Subsequently they performed a 10Km running trial and t10Km was related to HRV and HRR indexes. The time to perform a 10Km running trial was significantly correlated with baseline HRV indexes. No correlation was found between t10Km and HRR. Baseline HRV measures, but not HRR, were significantly correlated with the time of performance on 10km running in "master" athletes. The enhanced parasympathetic function at rest appears to be a condition to a better performance on 10km running. HRV can be simple and useful measurements for monitoring the training stratus of athletes and their physical condition in proximity of a competition.